Scott and Bailey. Season four [videorecording (DVD)] - Bullmore, Amelia, 1964-; Bullmore, Amelia, 1964-; Jones, Suranne, 1978-; Sharp, Lesley, 1964- (BBC Worldwide, 2015)
Battle-scarred from their conflict, Rachel and Janet decide to move forward with focus and honesty. But when they both pass the promotion board with flying colours, it falls to Gill to choose who stays on as Sergeant at Syndicate 9, and their newfound harmony is threatened. Rachel's self-doubt sees her struggle with balancing her ambition with a new relationship, which may just be the best she's ever had. Meanwhile, Janet's home life throws up some parental challenges, and a fatal error puts her under investigation for the first time in her career. In the face of a threat to their brilliant mentor DSI Gill Murray, Scott and Bailey are determined to get her over the finish line to retirement with her phenomenal reputation in tact.